(untitled) (Boletin Médico de Postgrado, 2020)
In the pediatric emergency room it is essential to recognize the clinical signs that indicate the threat of the patient’s condition on time. In order to establish the usefulness of the Pediatric Assessment Triangle (PET) in pediatric patients who attended the Emergency Service of the Servicio Desconcentrado Hospital Pediátrico Dr. Agustin Zubillaga during the period March-April 2018, a cross-sectional descriptive study was conducted with a total of 216 patients, with an average age of 2,98 ± 3,06 years, of which 36,11% were under one year old and 22,69% infants were one to two years old, with a slight predominance of males (53,70%). According to each component of the PET, 61,54% of patients had alterations in their appearance and general state, language (61,54%), state of consciousness (53,85%) and tone (50%). With respect to the work of breathing, subcostal retractions prevailed (86,21) as well as intercostal retractions (34,48%), expiratory moans (24,14%) and difficulty in speaking (17,24%). For the circulation part of the PET, pallor was register in mucous membranes (91,86%) and skin (54,05%). The physiopathological diagnoses were stability in 68,98% of cases, 9,26% had respiratory difficulty and 9,72% had compensated shock. The decision of admission was made in 13,89% of cases while 86,11% of cases were managed in an ambulatory manner. This study provides relevant information of the Pediatric Assessment Triangle as a useful tool to identify and classify the severity of a pediatric emergency in our hospital.